2015
DOI: 10.1615/computthermalscien.2015012298
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Investigation of Effects of Flow-Field Geometry on Transient Performance of an Automotive Polymer Electrolyte Membrane Fuel Cell

Abstract: A three-dimensional, multi-species, multi-phase PEM fuel cell model was developed in order to investigate the effect of the flow-field geometry on the steady-state and transient performances of the cell under an automotive operation. The two most commonly used designs, parallel and single-serpentine flow-fields, were selected as they offer distinctive species transport modes of diffusion-dominant and convection-dominant flows in the porous layers, respectively. It was found that this difference in flow mode si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…-Low-to-zero cell skewness and close-to-unity cell orthogonality for good convergence rate. The governing equations and operating conditions are the same as used in the authors' previous publications [3,4] and Fluent Fuel Cells module manual [5]which not be repeated here. The problem is solved in a commercial CFD code, ANSYS Fluent with a PEM fuel cells add-on package.…”
Section: Methodsmentioning
confidence: 99%
“…-Low-to-zero cell skewness and close-to-unity cell orthogonality for good convergence rate. The governing equations and operating conditions are the same as used in the authors' previous publications [3,4] and Fluent Fuel Cells module manual [5]which not be repeated here. The problem is solved in a commercial CFD code, ANSYS Fluent with a PEM fuel cells add-on package.…”
Section: Methodsmentioning
confidence: 99%
“…The anode and cathode streams are humidified hydrogen and air, respectively. The governing equations used in this study are the ones used and explained in the authors' previous publications [19]- [21] and Fluent Fuel Cells module manual [22] hence not repeated here. The operating conditions are given in Table 2 while properties of all meshes are summarised in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…System boundary Computational domain CFD software Shimpalee and Dutta 10 Single flow channel with GDL and MEA Single domain Fluent Berning and Djilali 11 Single flow channel with GDL and MEA Multi-domain CFX Mazumder and Cole 12 Single flow channel with GDL and MEA Single domain CFD-ACEþ Coppo et al 13 Single flow channel with GDL and MEA Single domain CFDesign Matamoros and Bruggemann 14 Single flow channel with GDL and MEA Single domain Own written codes Al-Baghdadi and Al-Janabi 15 Single flow channel with GDL and MEA Multi-domain Unspecified Schwarz and Djilali 16 Single flow channel with GDL and MEA Single domain Fluent Shimpalee et al 17 Complete cell Single domain STAR-CD Jang et al 18 Complete cell Single domain Unspecified Ren et al 19 Double flow channels with GDL and MEA Single domain Unspecified Wang 20 Single flow channel with GDL and MEA Single domain Own written codes Wang et al 21 Single flow channel Single domain Fluent Berning et al 22 Single flow channel with GDL and CL Multi-domain unspecified Schwarz and Beale 23 Complete cell Single domain Fluent Schwarz and Djilali 24 Single flow channel with GDL and MEA Single domain Fluent Berning et al 25 Single flow channel with GDL and MEA Multi-domain CFX Yuan et al 26 Single flow channel with GDL and MEA Single domain Fluent Wu et al 27 Single flow channel with GDL and MEA Single domain Fluent Cordiner et al 28 Single flow channel with GDL and MEA Multi-domain Fluent Fink and Fouquet 29 Complete cell Multi-domain AVL FIRE Kang et al 30 Complete cell Single domain Fluent Chiu et al 31 Single flow channel with GDL and MEA Single domain CFD-ACEþ Sun et al 32 Single flow channel with GDL and MEA Multi-domain Own written codes Cao et al 33 Single flow channel with GDL and MEA Single domain Own written codes Hossain et al 34 Single flow channel with GDL and MEA Single domain Fluent Jiang and Wang 35 Single flow channel with GDL and MEA Single domain Fluent Mancusi et al 36 Single flow channel with GDL and MEA Single domain Fluent Choopanya and Yang 37 Complete cell Singl...…”
Section: Refmentioning
confidence: 99%
“…Choopanya and Yang 37 developed a multiphase model to investigate the effect of the parallel and the serpentine flow-field geometries on the cell performance under both steady-state and transient operations. It was found that in the steady-state run, the average current density increases with the use of a serpentine flow field due to superior water removal ability.…”
Section: Literature 3d Multiphase Flow Cfd Modelsmentioning
confidence: 99%